Pengelolaan Arsip Dinamis Inaktif di Kantor Dinas Koperasi dan Usaha Mikro Kecil dan Menengah (UMKM) Provinsi Sumatera Barat - Yanti, Rani Nova; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2014)
Writing this article aims to: (1) describe the creation of the archive in the Office of Cooperative and Small and Medium Enterprises (SMEs) of the province of West Sumatra; (2) describe the use and maintenance of records in the Office of Cooperative and Small and Medium Enterprises (SMEs) of the province of West Sumatra; (3) describe the depreciation records in the Office of Cooperative and Small and Medium Enterprises (SMEs) of the province of West Sumatra. Based on the discussion, it can be concluded: (1) the creation of records in the Office of Cooperative and Small and Medium Enterprises (SMEs) of the province of West Sumatra there is no serious problem that occurs due to the life cycle of records; (2) the use and maintenance in the Office of Cooperative and Small and Medium Enterprises (SMEs) of the province of West Sumatra has a limited budget so that funds infrastructure not materialize; (3) depreciation records in the Office of Cooperative and Small and Medium Enterprises (SMEs) of the province of West Sumatra has not been done because each unit to keep its own archives. Keywords: management; dynamic; active; cooperative; micro